Who Benefits Most from the Family Education and Support Program in Cape Verde? A Cluster Analysis - Adriana Correia; Cátia Martins; Rita dos Santos; Victoria Hidalgo; Saúl Neves de Jesus; Cristina Nunes (MDPI AG, 2024)
Background/Objectives: Child parenting programs can enhance parental skills, prevent future issues in child development, and improve children's quality of life. The present research aimed to study the changes promoted by the Family Education and Support Program (FAF) implemented in Cape Verde, regarding parental educational practices, perceived parental efficacy, and attitudes and beliefs of Cape Verdean parents. Methods: To this end, 37 participants were evaluated through a pretest-postest design. The evaluated dimensions were perceived parental competence, parenting practices, Parental attitudes and beliefs, mental health and perceived child quality of life. Results: A cluster analysis was conducted, distinguishing two groups. Both groups benefited from the program. Cluster 1 reported more significant gains in dimensions of parental efficacy and satisfaction, inadequate expectations, affection and support, and reactivity, while cluster 2 showed a greater difference in regulation and reactivity. Conclusions: Overall, the FAF intervention contributed to an increase in positive parenting practices. By analyzing potential underlying profiles in the change process, this study suggests that there are participants who benefit more than others from the intervention, and this information may be relevant for professionals and researchers in the field.